Causal roles of circulating cytokines in sarcopenia-related traits: a Mendelian randomization study - Chen, Zhi; Sun, Jun; Shi, Tengbin; Song, Chenyang; Wu, Chengjian; Wu, Zhengru; Lin, Jiajun (Frontiers in Endocrinology, 2024)
Background: Epidemiological and experimental evidence suggests that chronic inflammation plays an important role in the onset and progression of sarcopenia.However, there is inconsistent data on the inflammatory cytokines involved in the pathogenesis of sarcopenia. Therefore, we performed a two-sample Mendelian randomization (MR) analysis to explore the causal relationship between circulating cytokines and sarcopenia-related traits.The MR analysis utilized genetic data from genome-wide association study that included genetic variations in 41 circulating cytokines and genetic variant data for appendicular lean mass (ALM), hand grip strength, and usual walking pace. Causal associations were primarily explored using the inverse variance-weighted (IVW) method, supplemented by MR-Egger, simple mode, weighted median, and weighted mode analyses. Additionally, sensitivity analyses were also performed to ensure the reliability and stability of the results.Three cytokines [hepatocyte growth factor (HGF), interferon gamma-induced protein 10 (IP-10), and macrophage colony-stimulating factor (M-CSF)] were positively associated with ALM (β: 0.0221, 95% confidence interval (CI): 0.0071, 0.0372, P= 0.0039 for HGF; β: 0.0096, 95%CI: 4e-04, 0.0189, P= 0.0419 for IP-10; and β: 0.0100, 95%CI: 0.0035, 0.0165, P= 0.0025 for M-CSF). Conversely, higher levels of interleukin-7 (IL-7), monocyte chemotactic protein 3 (MCP-3), and regulated on activation, normal T cell expressed and secreted (RANTES) were associated with decreased hand grip strength (β: -0.